PERANCANGAN PUSAT TEKNOLOGI & INFORMASI DI KABUPATEN TOJO UNA-UNA DENGAN PENDEKATAN SMART BUILDING - Musa, Lutfi Alfia S.; Bakhtiar, Bakhtiar (Universitas Bina Taruna Gorontalo, 2022)
Information and technology center design as a place to communicate and interact with various SKPD/offices, information and technology development centers and shopping centers that aim to build social interaction between communities. The design of the information and technology center is carried out by applying the Smart Building approach. The Smart Building design concept is the utilization of natural energy and artificial energy. Energy efficiency in lighting and ventilation systems using the latest technological materials, which refer to structures, sensor systems and digitization. The design location is in Ampana City because it is the capital of the Tojo Una-una Regency, besides that it has an amazing and sustainable beach view. While the site is on Jl. Ahmad Yani, Dondo, Ampana Kota District, because it is very strategic according to the characteristics of this area. The shape of the Information and Technology Center in Tojo Una-Una Regency takes the Smart Building concept. Buildings that use smart building principles with a modern appearance are adapted to the building materials used and the responsibility of smart building materials to the local climate conditions.